Mathematical Modeling of Multi-sized Argon Gas Bubbles Motion and Its Impact on Melt Flow in Continuous Casting Mold of Steel - LIU, Chong-lin; LUO, Zhi-guo; ZHANG, Tao; DENG, Shen; WANG, Nan; ZOU, Zong-shu (Journal of iron and steel research, international, 2014)
The 3D turbulence k-ε model flow of the steel melt （continuous phase） and the trajectories of individual gas bubbles （dispersed phase） in a continuous casting mold were simulated using an Eulerian-Lagrangian approach. In order to investigate the effect of bubble size distribution, the radii of bubbles are set with an initial value of 0. 1- 2.5 mm which follows the normal distribution. The presented results indicate that, in the submerged entry nozzle （SEN）, the distribution of void fraction is only near the wall. Due to the fact that the bubbles motion is only limited to the wall, the deoxidization products have no access to contacting the wall, which prevents clogging. In the mold, the bubbles with a radius of 0. 25--2.5 mm will move to the top surface. Larger bubbles issuing out of the ports will attack the menis- cus and induce the fluid flows upwards in the top surface near the nozzle. It may induce mold powder entrapment into the mold. The bubbles with a radius of 0.1--0.25 mm will move to the zone near the narrow surface and the wide surface. These small bubbles will probably be trapped by the solidification front. Most of the bubbles moving to the narrow surface will flow with the ascending flow, while others will flow with the descending flow.